30-Day Mortality after Haemodialysis Vascular access Surgery: A Retrospective Observational Study. Issue 3 (May 2016) - Jorna, Thomas; Methven, Shona; Ravanan, Rommel; Weale, Andrew R.; Mouton, Ronelle
Purpose: The prevalence of haemodialysis is increasing globally. There is a consensus of international opinion that permanent vascular access is preferred for haemodialysis. Patients with end-stage renal disease carry a high burden of cardiovascular comorbidity. There is a lack of data to quantify the post-operative risk of vascular access surgery. This study looked to establish the 30-day post-operative mortality for patients undergoing surgery to create vascular access and to measure for differences between the types of access created and the mode of anaesthesia. Methods: We conducted a retrospective study of all cases over a 5-year period at a tertiary renal unit in the UK. Data recorded included co-morbidity, time on renal replacement therapy, type of access created, mode of anaesthesia and 30-day mortality. The incident risk was calculated and logistic regression used to calculate the adjusted odds ratio. Results: A total of 1404 operations were included. 30-day mortality for the whole cohort was 1.1% (16/1404). The adjusted odds ratio of death at 30 days using an upper limb fistula as a reference was 5.27 for an upper limb graft (p = 0.005) and 11.51 (p = 0.007) for any lower limb access. Using local anaesthesia as a reference the adjusted odds ratio for surgery under general anaesthesia was 6.28 (p = 0.001). Conclusions: Vascular surgery for haemodialysis is associated with significant and variable post-operative mortality; this study highlights the need for careful pre-operative planning in this complex group of patients.